Strategien der deutschen und französischen Ernährungsindustrie und deren Auswirkungen auf die Wettbewerbsposition; Strategies of the German and French food industry and consequences for the competitiveness - Hannes Weindlmaier; Jean-Louis Floriot (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– Based on an analysis of selected determinants for the competitiveness and of strategies of the food industries the contribution illustrates similarities and major differences between the food industries of these two countries. It is shown that in both countries measures are necessary to further improve competitiveness. Important strategic means are the continuation of structural change, the strengthening of the position of co-operatives, a consequent orientation towards market developments and a stronger internationalisation.
Keywords: 330; Ernährungsindustrie; Vergleich; Lebensmittelhandel; Deutschland; Frankreich